Children from the other America : a crisis of possibility - Levy, Michele López-Stafford (Transgressions (Rotterdam, Netherlands) ;, 2016)
"Necessity is the mother of invention and this all began with a plea on a listserv: 'We have a sixteen year old Mayan Quiche young man who won't stop crying in our school'. How desperate must a parent be to say goodbye to their child/children to perhaps never see them again because of wars in Syria or gang violence in Central America making citizens so desperate? Will the children make it alive to the next border with so many more to cross? Will they really eventually meet up with family? Or is this pure folly? Will these children be able to go to school for an equitable education and have a much better life than their parents could ever imagine? More important are the implications for U.S. schools: how are they managing the sudden influx of children refugees who are road weary and expected to participate in school structures seamlessly? Many are not aware that, linguistically, these children may not be Spanish-speaking, but only communicate in their own Indigenous language"--Provided by publisher